Thalamocortical Connections between the Mediodorsal Nucleus of the Thalamus and Prefrontal Cortex in the Human Brain: A Diffusion Tensor Tractographic Study - Jang, Sung Ho; Yeo, Sang Seok (Yonsei medical journal, 2014)
The elucidation of thalamocortical connections between the mediodorsal nucleus (MD) of thalamus and the prefrontal cortex (PFC) is important in the clinical fields of neurorehabilitation and psychiatry. However, little is known about these connections in human brain. We attempted to identify and investigate the anatomical characteristics of the thalamocortical connection between MD and PFC in human brain using diffusion tensor tractography (DTT). Thirty-two healthy volunteers were recruited for this study. Diffusion tensor images were scanned using a 1.5-T. A seed region of interest was placed at the MD of the thalamus on coronal images, and target regions of interest were placed on the dorsolateral prefrontal cortex (DLPFC), the ventrolateral prefrontal cortex (VLPFC), and the orbitofrontal cortex (OFC), respectively. The three thalamocortical connections found were reconstructed using Functional Magnetic Resonance Imaging of the Brain (FMRIB) software. The three thalamocortical connections were arranged in subcortical white matter in the following order from upper to lower levels: the DLPFC, the VLPFC, and the OFC. In terms of fractional anisotropy and mean diffusivity values, no significant differences were observed between the DLPFC, VLPFC and OFC (p>0.05). In contrast, the OFC tract volume was higher than those of the DLPFC and the VLPFC (p<0.05). Three thalamocortical connections were reconstructed between MD and PFCs in human brain using DTT. We believe that the results of this study would be helpful to clinicians in treating frontal network syndrome and psychiatric diseases.